Synthesis of MnFe2O4 Nanoparticles as a Basic Material for Microwave Absorber - Rahmayanti, Rika; Sudiati, Sudiati (Journal of Technomaterial Physics, 2022)
This work aimed to synthesize MnFe2O4 nanoparticles using the coprecipitation method. Manganese chloride dihydrate (MnCl2.4H2O) and iron sand from South Cianjur, Indonesia, were used as a precursor for MnFe2O4 nanoparticle synthesis. The iron sand elements and compounds were tested using X-Ray Fluorescence (XRF). MnFe2O4 nanoparticle was characterized using X-Ray Diffraction (XRD), Scanning Electron Microscope-Energy Dispersive X-Ray (SEM-EDX), and Vector Network Analyzer (VNA). The X-Ray Fluorescence test result showed that 70.54% of South Cianjur contained iron sand. The SEM test result showed that the nanoparticles have an average size of Â 73.75 nm with a round shape, which was attributed to the agglomeration process. The EDX test result showed that the synthesized nanoparticle contained only Mn, Fe, and O elements without contaminants. The XRD test result showed that the crystal phase of MnFe2O4 was formed with a crystal size of less than 27 nm. The largest reflection losses in the 11.5 - 12.5 GHz range were found in MnFe2O4 with 1:2 variation, i.e., 35.08 dB. This study found that adding iron sand increases MnFe2O4 microwave absorption.